ANALISIS PENGEMBANGAN WILAYAH DAN SEKTOR POTENSIAL GUNA MENDORONG PEMBANGUNAN DI KOTA SALATIGA - Wijaya, Bayu; Atmanti, Hastarini Dwi (PRESTASI, 2009)
Economic development is a process to change the situation to become better. Economic development is a process of increasing income, employment and community prosperity. Economic growth can be used as a measure of regional economic development. Research was conducted in the city of Salatiga. Salatiga city has a very strategic location between Semarang and Surakarta. Salatiga have the facilities and resources that can support economic development. The economic growth is high compared with other regions in the surrounding areas, but the value of GDP is the lowest in Central Java Province. This research is related to the condition of Salatiga during the period 1994-2002. This study aims to identify strategic sectors in the city of Salatiga, which can further be developed to further increase the GDP in order to further increase economic growth to support economic development regions. Key words: economic growth, potential sector.